Gold nanoconjugates reinforce the potency of conjugated cisplatin and doxorubicin - Iram, S. (Colloids and Surfaces B: Biointerfaces, 2017)
Osteosarcoma or osteogenic sarcoma is the most common and prevalent cancerous tumor of bone and occurs especially in children and teens. Recent treatment strategy includes a combination of both chemotherapy and surgeries. Although, the use of single drug-based chemotherapy treatment remains unsatisfactory. Therefore, combinatorial therapy has emerged as a potential strategy for treatment with limited side- effects. Here, we evaluated the combinatorial anticancerous effect of cisplatin (CIS) and doxorubicin (DOX) bioconjugated bromelain encapsulated gold nanoparticles (B-AuNPs conjugated CIS and DOX) in the treatment of osteosarcoma. The synthesized B-AuNPs conjugated CIS and DOX were characterized by various characterization techniques like UV–vis spectroscopy, TEM, DLS and zeta potential to ensure the synthesis, size, shape, size distribution and stability. Drug loading efficiency bioconjugation of CIS and DOX was ensured by UV–vis spectroscopy. Bioconjugation of CIS and DOX was further confirmed using UV–vis spectroscopy, TEM, DLS, Zeta potential and FT-IR analysis. The combinatorial effect of CIS and DOX in B-AuNPs conjugated CIS and DOX showed highly improved potency against MG-63 and Saos-2 cells at a very low concentration where primary osteoblasts didn't show any cytotoxic effect. The apoptotic effect of B-AuNPs conjugated CIS and DOX on osteosarcoma and primary osteoblasts cells were analyzed by increased permeability of the cell membrane, condensed chromatin and deep blue fluorescent condensed nucleus. The results clearly showed that B-AuNPs conjugated CIS and DOX significantly improved the potency of both the chemotherapeutic drugs by delivering them specifically into the nucleus of cancer cells through caveolae-dependent endocytosis. Thus, the greater inhibitory effect of combinatorial drugs (B-AuNPs conjugated CIS and DOX) over single drug based chemotherapy would be of great advantage during osteosarcoma treatment.
Keywords: cells; chemotherapy; Cytology; Cytotoxicity; Drug interactions; dynamic light scattering; Gold; Molecular Biology; Platinum Compounds

Exploring the mechanisms of yoga-based cardiac rehabilitation in heart failure via assessment of endothelial function, genomics and arterial health (Yoga-EndOmics): a study protocol - Shetty, Vindya Vasu; Patil, Laxmi Ramchandra; Patil, Satish G.; Aithal, Kiran; Oli, Ajay Kumar; Yenagi, Vijay Aravind; Kaulgud, Ram S.; Dharne, Mahesh; Chandra Sekaran, Ambalam M.; Prabhakaran, Dorairaj (BMJ Open, 2026)
Introduction Heart failure (HF) remains a major global health challenge, particularly in low-resource settings where access to comprehensive cardiac rehabilitation (CR) is limited. Yoga, a culturally contextualised mind-body intervention, holds promise as an adjunctive therapy in CR. The Yoga-EndOmics study aims to evaluate the effects of Yoga-based cardiac rehabilitation (Yoga-CaRe) on gene expression, endothelial function, vascular biomarkers and clinical outcomes in systolic HF, providing mechanistic insights into its potential integration into conventional cardiac rehabilitation.Methods and analysis This is a prospective, randomised, open-label, blinded-endpoint (PROBE) mechanistic trial enrolling 78 patients with HF with reduced ejection fraction (HFrEF). Participants will be randomised in a 1:1 ratio to receive either a structured Yoga-CaRe intervention or enhanced standard care for 3 months. The Yoga-CaRe group will attend 20 supervised sessions with guided home practice involving tailored asanas, pranayama and meditation. Primary outcomes are changes in endothelial-dependent flow-mediated dilation (FMD) and functional exercise capacity at 3 months. Secondary outcomes include changes in arterial compliance and stiffness, circulating biomarkers of endothelial dysfunction, oxidative stress and inflammation, and immediate changes in global gene expression profiles in peripheral blood mononuclear cells following the Yoga-CaRe intervention. Data will be analysed using analysis of covariance (ANCOVA) for between-group comparisons and significant analysis of microarray (SAM) for global gene expression profiles.Ethics and dissemination The study has received ethical clearance from the Institutional Ethics Committee of the SDM College of Medical Sciences and Hospital, India (SDMIEC/2025/1072) and is registered with the Clinical Trials Registry of India. Findings will be disseminated through peer-reviewed journals, scientific conferences and stakeholder engagement platforms to inform future integrative strategies in HF management.Trial registration number CTRI/2023/12/060758
Keywords: DNA Methylation; Genetics; Heart failure; Molecular Biology; Randomized Controlled Trial